Effectiveness of Group Counseling Solution-Focused Brief Therapy (SFBT) To Reduce Abuse of Smartphones by Students - Mardatilla Mardatilla; Hasan Hasan; Ridwan Syahran; Mai Zuniati; As’ari Latief (Scidacplus, 2025)
This study aims to determine the effectiveness of group counseling services. Solution-focused brief Therapy (SFBT) to reduce smartphone abuse among students. The subjects in this study amounted to 12 samples, which became 2 groups, namely 6 samples in the experimental group and 6 samples in the control group. The data collection tool in this study was through the provision of a questionnaire on the abuse of smartphones. The data obtained was processed and analyzed using quantitative analysis, using the Mann-Whitney test. The results of the analysis show that before the provision of group counseling services, Solution-Focused Brief Therapy (SFBT), there are 2 students in the abuse level classifications smartphone moderate, and 4 students at the abuse level smartphone high classification. The results of the analysis using the Mann-Whitney test obtained a significance value of Sig. (2-tailed) of 0.024 < 0.05, then H0rejected Ha accepted. So, it can be proven that group counseling Solution-Focused Brief Therapy (SFBT) is effective in reducing smartphone misuse by students.